2019
DOI: 10.18632/aging.102481
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0006332 promotes growth and progression of bladder cancer by modulating MYBL2 expression via miR-143

Abstract: In this study, we analyzed the role of circular RNAs in the growth and progression of bladder cancer. Direct Sanger sequencing and quantitative RT-PCR analysis showed that circ_0006332 was significantly upregulated in bladder cancer tissues. Sequencing analysis showed that circ_0006332 is generated from splicing of exons 8 and 9 of the MYBL2 transcript. Fluorescence in situ hybridization analysis showed that circ_0006332 was localized to the cytoplasm of bladder cancer cells. Dual luciferase reporter assays sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
(32 reference statements)
1
13
0
Order By: Relevance
“…Furthermore, MYBL2 was one direct gene of miR‐423‐5p and elevated expression of miR‐423‐5p suppressed MYBL2 expression and ectopic expression of RPSAP52 increased MYBL2 expression in SCC‐4 cell. A previous study indicated that MYBL2 acted as one oncogene in tumour development 44,45 . Finally, we illustrated that RPSAP52 overexpression promoted TSCC cell growth and cycle and induced cytokine secretion including IFN‐γ, IL‐1β and IL‐6, IL‐8, IL‐10 and TGF‐β via modulating MYBL2.…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, MYBL2 was one direct gene of miR‐423‐5p and elevated expression of miR‐423‐5p suppressed MYBL2 expression and ectopic expression of RPSAP52 increased MYBL2 expression in SCC‐4 cell. A previous study indicated that MYBL2 acted as one oncogene in tumour development 44,45 . Finally, we illustrated that RPSAP52 overexpression promoted TSCC cell growth and cycle and induced cytokine secretion including IFN‐γ, IL‐1β and IL‐6, IL‐8, IL‐10 and TGF‐β via modulating MYBL2.…”
Section: Discussionsupporting
confidence: 55%
“… 11 , 12 For instance, Li et al indicated that circ_006332 contributed to bladder cancer development by regulating MYB Proto-Oncogene Like 2 expression. 13 Zhang et al also revealed that circ-phosphoglycerate mutase 1(circ-PGAM) promoted ovarian cancer growth via sponging microRNA-542-3p (miR-542-3p). 14 In addition, Xu et al demonstrated that circ_0004771 could regulate hypoxia-mediated 5-Fluorouracil resistance to gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNA (circRNA) is a noncoding RNA with closed loop. 7 An increasing number of studies have indicated that circRNA acted as a promoter or suppressor in cancer progression. 8,9 For instance, Yang et al revealed that circ_0049027 (circ_HuR) inhibited cell migration and invasion in vitro and in vivo; 8 Wu et al also explained that circ-ZNF609 contributed to the proliferation of colorectal cancer cells by sponging microRNA-150 (miR-150).…”
Section: Introductionmentioning
confidence: 99%